Validation of Androgen Receptor loss as a risk factor for the development of brain metastases from ovarian cancers - Gloria Mittica; Margherita Goia; Angela Gambino; Giulia Scotto; Mattia Fonte; Rebecca Senetta; Massimo Aglietta; Fulvio Borella; Anna Sapino; Dionyssios Katsaros; Furio Maggiorotto; Eleonora Ghisoni; et al. (Journal of Ovarian Research, 2020)
Abstract Background Central nervous system (CNS) spreading from epithelial ovarian carcinoma (EOC) is an uncommon but increasing phenomenon. We previously reported in a small series of 11 patients a correlation between Androgen Receptor (AR) loss and localization to CNS. Aims of this study were: to confirm a predictive role of AR loss in an independent validation cohort; to evaluate if AR status impacts on EOC survival. Results We collected an additional 29 cases and 19 controls as validation cohort. In this independent cohort at univariate analysis, cases exhibited lower expression of AR, considered both as continuous (p <  0.001) and as discrete variable (10% cut-off: p <  0.003; Immunoreactive score: p <  0.001). AR negative EOC showed an odds ratio (OR) = 8.33 for CNS dissemination compared with AR positive EOC. Kaplan-Meier curves of the combined dataset, combining data of new validation cohort with the previously published cohort, showed that AR <  10% significantly correlates with worse outcomes (p = 0.005 for Progression Free Survival (PFS) and p = 0.002 for brain PFS (bPFS) respectively). Comparison of AR expression between primary tissue and paired brain metastases in the combined dataset did not show any statistically significant difference. Conclusions We confirmed AR loss as predictive role for CNS involvement from EOC in an independent cohort of cases and controls. Early assessment of AR status could improve clinical management and patients’ prognosis.